Semissíntese de compostos bioativos a partir de produtos naturais: obtenção de derivados da estemodina - Oliveira, José Augusto Carneiro de (2021)
Derivatization of bioactive molecules from natural sources, aiming to improve physicochemical properties and optimize pharmacological properties, has been a valuable tool in discovering and developing new drugs. The connected correlation of semi-synthesis to results of natural products is reported in the literature. In this context, a species Stemodia maritima Linn., popularly known in the Northeast of Brazil as melosa, is rich in stemodin diterpene, which has analgesic, bactericidal, and bactericidal cytotoxic activities. Semi-synthetic derivatives and bioactive biotransformed of stemodin are described in the literature. However, oximes and their esters have not yet been reported. Therefore, the present study had the main objective to prepare oximes and semi-synthetic esters of stemodin and other derivatives. The analogs were semi- synthesized from oxidation, oximation, acylation and acetilation reactions. In the structural characterization of the compounds, physical (p.f.) and spectrometric data (1H and 13C NMR, IR, and high-resolution MS) were used, in addition to comparison with data from the literature. Twelve semi-synthetic derivatives were obtained, of which ten are unpublished. In vitro cytotoxic activity of stemodin, E/Z-oximes, and esters against human cancer cell lines (PC3, HCT-116, HL60, and SNB-19), showed promising results for esters OX1-Z1, OXI-E1, OXI- E2, and OXI-E3, with cell growth inhibition percentages (≥75%) higher than stemodin and positive control (doxorubicin) in at least one of the strains tested. In general, the E- stereoisomers of the E-oxime esters have better cytotoxic activities than the Z-stereoisomers of the Z-oxime esters, which suggests the need for structural activity relationship studies to determining the IC50 and evaluating the cytotoxicity in healthy cells of bioactive derivatives.